Reproductive potential of Ucides cordatus (Linnaeus, 1763) (Decapoda: Brachyura: Ocypodidae) from two mangrove areas subject to different levels of contaminants. Issue 1 (23rd November 2018) - João, Marcio C A; Pinheiro, Marcelo A A
Abstract: Ocypodid crabs are common in mangrove areas, and the uçá, Ucides cordatus (Linnaeus, 1763 ), is a key species. It is abundant and economically relevant in these marine wetlands on the southeastern Atlantic coast of Brazil. Mangroves suffer from intense anthropogenic impact by pollutants affecting the reproductive biology of the animals inhabiting this ecosystem. We analyzed the reproductive potential of U. cordatus, comparing fecundity and fertility equations between two mangroves with distinct pollution levels in São Paulo state, Brazil: a pristine (Juréia-Itatins Ecological Station) and a contaminated (Cubatão) area. There was no difference in egg production (fecundity) between crabs from both areas, possibly due to tolerance mechanisms exhibited by the crabs. There was, however, a substantial difference in larval production, which was three times higher in crabs from the contaminated mangrove than in those from the pristine mangrove. These results are explained by different reproductive conditions of the ovigerous females arising from the fertility analysis: primiparous (first spawning from the contaminated area) and multiparous females (second or subsequent spawning from the pristine area). Multiple spawning in the same reproductive season had not been previously reported for this species. Results, however, do not explain the relationship between environmental contaminants and fertility, which should be investigated in the future.